2015
DOI: 10.5539/ijef.v7n12p176
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Ownership Heterogeneity and Firm Performance: Evidence from Malaysia

Abstract: The roles of institutional owners in alleviating agency problem and its effect on firms have been studied extensively in corporate finance. However, these researches have mixed results because most have treated institutional owners as a homogenous group. Drawing on previous research, this study differentiates institutional owners as transient or dedicated owners. These two groups of institutional owners differ significantly in terms of size of holdings, purposes, goals as well as monitoring efforts. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
(77 reference statements)
3
8
0
Order By: Relevance
“…Therefore, monitoring conducted by institutional investors encourages managers to act in the interests of shareholders so as to reduce problems that occur within the company (Mussa, musová & debnárová, 2015). The presence of institutional owners is increasingly becoming an important external control mechanism in monitoring management to act on behalf of shareholders and company interests (Katan & Mat Nor, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, monitoring conducted by institutional investors encourages managers to act in the interests of shareholders so as to reduce problems that occur within the company (Mussa, musová & debnárová, 2015). The presence of institutional owners is increasingly becoming an important external control mechanism in monitoring management to act on behalf of shareholders and company interests (Katan & Mat Nor, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differentiating institutional investors into two groups, transient and dedicated owners, Katan and Mat Nor (2015) verified that, in general, the presence of institutional investors in the ownership structure of Malaysian companies had no effect on firm performance. 1 However, when the authors specifically analysed the transient ownership group, the results showed a significant influence on firm performance.…”
Section: Literature Reviewmentioning
confidence: 95%
“…2 In general, the hypothesis of the aforementioned studies maintains that since institutional investors do not form a homogenous group, their influence may also vary. Certain studies have used legal type classifications 3 to group these agents (Bushee, 2004;Katan and Mat Nor, 2015), while other studies have considered other factors, including the degree of investor independence, 4 investor country of origin and whether the investor is private or public (Brossard et al, 2013;Chen et al, 2007;Ferreira and Matos, 2008). However, several study approaches do not necessarily incorporate background information into the behaviour of institutional investors and disregard significant intra-group variation associated with the size and stability of ownership, sensitivity to current returns, and other factors associated with investment profile (Bushee, 1998(Bushee, , 2001Crane et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations